Geographic disparities in access to outpatient stroke rehabilitation in Texas - Joseph Wozny; Melissa Howard; Susan Doherty; Yenan Zhu; Kalyani Sonawane; Dorothea Parker; Lisa W. Thomas; Bukola Azeez; Ndi Chukwumerije; Susan Varghese; Nicholas Hoang; Suja S. Rajan; et al. (PLoS ONE, 2025)
Background Outpatient rehabilitation plays a vital role in providing post-discharge care for stroke survivors’ optimum recovery. Geographic variability in access to post-stroke rehabilitation care in rural areas is poorly understood. Methods This study used Medicare claims from 2016 to 2019 to estimate incidence of stroke discharges home and compared rehabilitation utilization rates after discharge from acute hospitalization in the state of Texas. We also examined spatial accessibility to post-discharge outpatient rehabilitation centers between rural and urban areas. We supplemented claims results with a survey to better understand locations where outpatient rehabilitation clinics provided services to stroke patients. Results After discharge from the hospital, patients from rural counties neighboring urban counties had lower adjusted predicted probabilities of using outpatient clinic services compared to urban areas. Patients with primary diagnosis codes of stroke sequelae: adjusted relative rate of 0.84 (CI: 0.76,0.93) with an adjusted rate difference of −0.05 (CI: −0.08, −0.02), cerebral infarction: adjusted relative rate of 0.82 (CI: 0.72,0.91) with adjusted rate difference of −0.04 (CI: −0.06,-0.02), hemorrhagic patients: adjusted relative rate of 0.81 (CI: 0.71,0.91) with an adjusted rate difference of −0.04 (CI: −0.06,-0.01). We did not find discernable differences between rural and urban areas for home health utilization or the combination of outpatient clinic services with home health as a single category. Estimates from a floating-catchment spatial accessibility model scaled from 0 (worst access) to 1 (best access) showed that, compared to urban counties, indices in rural not adjacent to urban counties were −0.16 (CI: −0.23, −0.08) lower and −0.14 (CI: −0.20, −0.08) lower in rural areas in counties adjacent to urban counties. Conclusions Compared to urban areas, rural areas have lower spatial access to and utilization of outpatient clinic services in the state of Texas.